Application of high-power ion beams to thin films deposition and stimulating mass transfer of previously implanted dopants in materials; Proceedings of the 15th International Conference on High-Power Particle Beams(BEAMS 2004), Saint-Petersburg, July 18-23, 2004 - Ryabchikov A. I. Aleksandr Ilyich; Matvienko V. M.; Petrov A. V.; Struts V. K.; Usov Y. P. Yuri Petrovich; Shlapakovski A. S. (2005, 2005)
The results of investigations concerning some applications of high-power ion beams (HPIBs) to materials surface modification are presented. For BPIB-based film deposition, the characteristics of obtained coatings were studied depending on deposition conditions. It has been shown that mechanical and adhesion properties of the films are improved with decreasing deposition rate. For the combined surface treatment comprising traditional ion implantation and BPIB irradiation, the mass transfer of implanted dopant was investigated at multiple implantation-irradiation cycles. It has been demonstrated that one can control the depth of occurrence and storage of the implanted dopant.